1983
DOI: 10.1530/jrf.0.0690659
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine growth retardation detected in several species by non-normal birthweight distributions

Abstract: The statistical distribution of birthweights in 64 litters of pigs, 48 litters of dogs, 59 litters of rabbits, 130 litters of rats and 46 litters of mice was examined. Birthweight followed a Gaussian or normal distribution in about two-thirds of the litters inspected, as judged visually using a normal probability plot, and by the W-test statistic. In the remainder, a single outlying observation in an otherwise normal sample was detected by Dixon's test, and/or a separate sub-population of low birthweight anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 10 publications
2
24
0
Order By: Relevance
“…2.1.1 Intra-uterine growth restriction and susceptibility to infection and disease Low-birth-weight piglets in litters with high variation in birth weights experience intra-uterine growth restriction (IUGR), usually resulting in physiological dysfunctions and an increase in neonatal morbidity and mortality (Wootton et al, 1983;Aucott et al, 2004). In addition, IUGR neonates are more susceptible to infection or environmental changes due to an ineffective immune system (Cromi et al, 2009;Zhong et al, 2012), and IUGR animals have abnormal differences in size and histopathology of the thymus (Cromi et al, 2009).…”
Section: Pre-weaning Mortalitymentioning
confidence: 99%
“…2.1.1 Intra-uterine growth restriction and susceptibility to infection and disease Low-birth-weight piglets in litters with high variation in birth weights experience intra-uterine growth restriction (IUGR), usually resulting in physiological dysfunctions and an increase in neonatal morbidity and mortality (Wootton et al, 1983;Aucott et al, 2004). In addition, IUGR neonates are more susceptible to infection or environmental changes due to an ineffective immune system (Cromi et al, 2009;Zhong et al, 2012), and IUGR animals have abnormal differences in size and histopathology of the thymus (Cromi et al, 2009).…”
Section: Pre-weaning Mortalitymentioning
confidence: 99%
“…Previous investigations had shown that, within the Institute herd, this method selects SGA as distinct from slightly small AGA animals (25). When birth weight is plotted against the cumulative sample proportion on normal probability paper, a litter without an SGA animal presents a single straight line, whereas SGA piglets appear as clear deviates from this line (26,27).…”
Section: Animalsmentioning
confidence: 99%
“…Therefore, they are susceptible to mortality and morbidity, developing cerebral palsy, hyaline membrane disease, apnea, intracranial hemorrhage, sepsis, retrolental fibroplasia, growth and neurocognitive deficiencies [2]. Low birth weight can result from either a short gestation period or retarded intrauterine growth (or a combination of both) [2] as reported for humans and animals of many polytocous species, including dogs [3]. Based on evidence of embryo transfer studies in the human, horse and sheep, the intrauterine environment in which the fetus develops seems to exert a profound effect on birth weight, suggesting a central maternal role in determining the birth weight [4].…”
Section: Introductionmentioning
confidence: 99%